INCREASING THE REGIONAL INVESTMENT ATTRACTION BY PREPARING AND HOLDING OF LARGE SPORTS EVENTS - V. A. Leonov (Russian Journal of Economics and Law)
The work is devoted to the study of the regional investment attraction factors, as well as grounding the modern techniques of its increasing by holding large sports events of international scale by the example of Universiade 2013 in Kazan.